PENGARUH INFLUENCER INSTAGRAM DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN UMKM MINEWEAR: STUDI PADA UMKM MINEWEAR DI JAKARTA - Verdiananta, Lanang Dmitri; Kramadibrata, Budi (Lembaga Pengembangan Kinerja Dosen, 2023)
Promotional activities in the current era are very different from promotional activities in the past, in the midst of the disruption of the media and digital economy, now marketing activities have greatly evolved, including advertising on social media such as YouTube, Instagram, Facebook, Twitter and various other social media. This study aims to determine the effect of Instagram influencers and prices on purchasing decisions at Minewear SMEs. This research was conducted using a quantitative approach and associative research design with a total sample of 155 respondents. The instrument used by researchers is a questionnaire. Testing the quality of the research instrument, namely testing the validity and reliability. Data analysis used descriptive analysis, while for testing the hypothesis using multiple linear regression analysis. The results of this study explain that there is a positive and significant relationship between Instagram influencers and prices on purchasing decisions at MSMEs Minewear with a correlation coefficient value. This analysis is only carried out on one MSME and does not take into account other variables or moderator variables that influence purchasing decisions.